Composite jerk feedforward and disturbance observer for robust tracking of flexible systems. (June 2017) - Chen, Si-Lu; Li, Xiaocong; Teo, Chek Sing; Tan, Kok Kiong
Abstract: In this paper, a novel feedforward controller for flexible motion systems is proposed based on both the rigid-body mode and lump-sum of the flexible modes. It only requires the reference trajectory to be defined up to its jerk, and gives well-behaved high-pass feedforward sensitivity. For systems with severe low-frequency disturbance, an additional disturbance observer is introduced, using the same jerk feedforward as the inversion of the nominal model. Remarkably, with such proposed control scheme and novel loop-shaping criteria, the improvement of disturbance rejection and profile tracking does not result in obvious degrading of the noise attenuation.